Comparative Health Analysis of the National Bank, Joint Venture Banks and Foreign Banks in Indonesia - Rudianto, Dudi (Penerbit Universiti Utara Malaysia, 2017)
The Risk-Based Bank Rating approach (RBBR) is used to determine the health of banks in Indonesia, both for national banks, joint venture banks and foreign banks. This approach uses five (5) proxies, i.e. Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Net Interesr Margin (NIM), and the Capital Adequacy Ratio (CAR). The overall result of the 5 (five) variables studied show that national banks are healthier than the other two types of banks, namely venture banks and foreign banks, because the national bank has a value beyond the provisions of Bank Indonesia. The partial variable LDR consistently varies significantly between national banks, joint venture banks and foreign banks. The LDR of joint venture banks and foreign banks is higher than the national bank. These conditions indicate that the bargaining position of joint venture banks and foreign banks in serving the needs of public borrowing is much higher than the national bank, which results in increasing the ability of both types of banks in generating profit. Simultaneously throughout the study variables was significantly different among the national banks, joint venture banks and foreign banks.